Amphoteric behavior of di-2-pyridyl ketone benzoylhydrazone in ethanol-water mixtures* - Gaubeur, Ivanise; Rossi, Maura Vincenza; Iha, Koshun; Suárez-Iha, Maria Encarnación Vázquez (Eclética Química, 2000)
The ligand di-2-pyridyl ketone benzoylhydrazone (DPKBH) is widely used for the determination of transition metal ions in environmental samples. Due to its low solubility in water it is used in aqueous-ethanol (1:1) solvent and for higher sensitivity the pH must be properly adjusted. The properties of DPKBH solutions must be known at different ethanol-water percentages in order to achieve higher sensitivity and/or selectivity for metal analysis. The acid-base behavior of this reagent in aqueous-ethanol solvent and the dissociation/ionization constants (pK1 and pK2) of DPKBH have been determined in different aqueous-ethanol solvent mixtures (10, 20, 30 and 50 % V/V of ethanol) from potentiometric titrations at 25.0 ± 0.1° C. As the amount of ethanol increases from 10 to 30% the pK1 and pK2 values increased, but they decreased in 50% of the organic solvent. The results are correlated with the medium composition and its effects.